Surgeons’ early experience with the Acessa™ procedure: gaining proficiency with new technology - Braun KM; Sheridan M; Latif EZ; Regush L; Maksymowicz A; Weins L; Bedaiwy MA; Tyson N; Davidson MJ; Sanders BH (Dove Medical Press, 2016)
Kelli M Braun,1 Mark Sheridan,2 Erin Z Latif,1 Lexy Regush,3 Anet Maksymowicz,4 Laura Weins,5 Mohamed A Bedaiwy,6 Nerissa Tyson,5 Marilyn J Davidson,2 Barry H Sanders7 1Department of Obstetrics and Gynecology, Medical College of Georgia at Augusta University, Augusta, GA, USA; 2Department of Obstetrics and Gynecology, Saskatoon Obstetric and Gynecologic Consultants, 3Department of Obstetrics and Gynecology, Royal University Hospital, Saskatoon, 4Department of Obstetrics and Gynecology, Regina General Hospital, Regina, 5Department of Obstetrics and Gynecology, University of Saskatchewan, Saskatoon City Hospital, Saskatoon, SK, 6Department of Obstetrics and Gynecology, British Columbia Women’s Hospital, Vancouver, 7Department of Obstetrics and Gynecology, Division of General Gynaecology and Obstetrics and Division of Gynaecologic Specialties, Vancouver General Hospital, Vancouver, BC, Canada Purpose: Successful adoption of a new surgical procedure varies among practicing surgeons, and skill acquisition depends on the surgeon’s innate ability, the complexity of the technique, and training. We report intraoperative and near-term postoperative outcomes from the Acessa procedure conducted by minimally invasive gynecologic surgeons new to Acessa, and report the surgeons’ experiences during the training period.Patients and methods: The study was designed as a postmarket, prospective, single-arm, multicenter analysis of operative and early postoperative outcomes after proctored surgical training with the Acessa device and procedure (laparoscopic ultrasound-guided radiofrequency volumetric thermal ablation of symptomatic fibroids) in premenopausal, menstruating women as conducted in community and university hospitals in the USA and Canada. Surgeons completed evaluation forms once they felt they could safely and comfortably conduct the operations.Results: Ten gynecologic surgeons without prior Acessa experience completed 40 Acessa procedures – all on an outpatient basis. Mean procedure time was 1.9±1.0 hours and was similar to that reported in the pivotal premarket study (2.1±1.0 hours). Two intraoperative complications occurred: a 1 cm uterine serosal laceration due to uterine manipulation and blood loss from both the probe insertion site and the lysis of uterine-omental adhesions. No postoperative complications or reinterventions for fibroid symptoms were reported. The surgeons completed the evaluation forms after two to five cases, and none found any factors affecting procedure efficiency to be inferior or needing improvement.Conclusion: Minimally invasive gynecologic surgeons new to Acessa can perform the procedure and provide acceptable outcomes after two to five proctored cases. Keywords: myoma, fibroid, leiomyoma, laparoscopic ultrasound, education, radiofrequency ablation